Adapting the First Aid education and response to the COVID-19 pandemic crisis (International Journal of First Aid Education)
Arguing that spreading First Aid knowledge and conducting trainings must always be ongoing in all times and should never be stopped, not even during the COVID-19 pandemic crisis or other crises, the letter offers a technical guidance note, developed as a suggestion for consideration in adapting curriculum, response, and mode of education, to continue all the efforts aimed at saving lives and assisting the most vulnerable in times of crisis, while putting the safety of the staff, volunteers, emergency responders, and all First Aid providers at the heart of the whole process.